Neuroimaging in mental health care: voices in translation - Borgelt, Emily L.; Buchman, Daniel Z.; Illes, Judy (Frontiers in Human Neuroscience, 2012)
Images of brain function, popularly called “neuroimages,” have become a mainstay of contemporary communication about neuroscience and mental health. Paralleling media coverage of neuroimaging research and the high visibility of clinics selling scans is pressure from sponsors to move basic research about brain function along the translational pathway. Indeed, neuroimaging benefit mental health care with early or tailored intervention, opportunities for education and planning, and access to resources afforded by objectification of disorder. However, risks of premature technology transfer, such as misinterpretation, misrepresentation, and increased stigmatization, could compromise patient care. Stakeholder views on neuroimaging for mental health care are a largely untapped resource of information and guidance for translational efforts. We argue that the insights of key stakeholders – researchers, healthcare providers, patients, and families - have an essential role to play upstream in professional, critical, and ethical discourse about neuroimaging in mental health. Here we integrate previously orthogonal lines of inquiry involving stakeholder research to describe the translational landscape as well as challenges on its horizon.